Thermostability enhancement and change in starch hydrolysis profile of the maltohexaose-forming amylase of Bacillus stearothermophilus US100 strain - Ben Ali, Mamdouh (Portland Press Ltd., 2006)
The implications of Asn(315) and Val(450) in the atypical starch hydrolysis profile of Bacillus stearothermophilus Amy (α-amylase) US100 have been suggested previously [Ben Ali, Mhiri, Mezghani and Bejar (2001) Enzyme Microb. Tech. 28, 537–542]. In order to confirm this hypothesis, three mutants were generated. Of these two have a single mutation, N315D or V450G, whereas the third contains both mutations. Analysis of the starch breakdown-profile of these three mutants, as well as of the wild-type, allowed us to conclude that each single mutation induces a small variation in the hydrolysis product. However, the major end product produced by the double mutant shifts from maltopentaose/maltohexaose to maltose/maltotriose, confirming the involvement of these two residues in starch hydrolysis. The superimposition of AmyUS100 model with that of Bacillus licheniformis shows in AmyUS100 an additional loop containing residues Ile(214) and Gly(215). Remarkably, the deletion of these two residues increases the half-life at 100 °C from 15 min to approx. 70 min. Moreover, this engineered amylase requires less calcium, 25 p.p.m. instead of 100 p.p.m., to reach maximal thermostability.